ANALISIS IMPLEMENTASI DATA SECURITY, INTENTION FOR COMPLIANCE, DAN KERANGKA COBIT DI PERUSAHAAN: TINJAUAN LITERATUR SISTEMATIS - Rohmah, Fadia Nur; Erliana, Siska; Aisy Su'udi, Abyan Haq; Asrar, Mohammad Masdarul (Universitas Negeri Surabaya, 2023)
One way to protect organizational data is to comply with security standards set by regulations and industry standards. The purpose of this compliance is to ensure that the organization meets the security requirements set by the competent authorities and avoids the risk of penalties or sanctions for breaches of privacy and data security. COBIT (Control Objectives for Information and Related Technology) is an IT management framework used by organizations to ensure that data security and privacy are well maintained. The purpose of this research is to find out the forms of implementation of data security management, intention for compliance with the COBIT framework in companies over the last 10 years. This research is expected to provide a scientific contribution to the direction of research in the field of data security management and provide managerial contributions regarding the urgency and challenges of COBIT implementation as part of good IT governance.